A case of antiphospholipid antibody syndrome with Budd-Chiari and colonic ulcers complicated with gastrointestinal hemorrhage - Özer İLKGÜL,; Gökhan İÇÖZ,; Murat DAYANGAÇ,; Yaman TOKAT,; Ömer ÖZÜTEMİZ, (Turkish Journal of Gastroenterology, 2019)
-